Differential effects of inotropes and inodilators on renal function in acute cardiac care. (15th May 2020) - Zima, Endre; Farmakis, Dimitrios; Pollesello, Piero; Parissis, John T
Abstract: Pathological interplay between the heart and kidneys is widely encountered in heart failure (HF) and is linked to worse prognosis and quality of life. Inotropes, along with diuretics and vasodilators, are a core medical response to HF but decompensated patients who need inotropic support often present with an acute worsening of renal function. The impact of inotropes on renal function is thus potentially an important influence on the choice of therapy. There is currently relatively little objective data available to guide the selection of inotrope therapy but recent direct observations on the effects of levosimendan and milrinone on glomerular filtration favour levosimendan. Other lines of evidence indicate that in acute decompensated HF levosimendan has an immediate renoprotective effect by increasing renal blood flow through preferential vasodilation of the renal afferent arterioles and increases in glomerular filtration rate: potential for renal medullary ischaemia is avoided by an offsetting increase in renal oxygen delivery. These indications of a putative reno-protective action of levosimendan support the view that this calcium-sensitizing inodilator may be preferable to dobutamine or other adrenergic inotropes in some settings by virtue of its renal effects. Additional large studies will be required, however, to clarify the renal effects of levosimendan in this and other relevant clinical situations, such as cardiac surgery.